The english picture book on intercultural awareness of Malaysian kindergateners. - Vijayaletchumy, Subramaniam; Abd Rahim, Normaliza; Nik Muhamad Affendi, Nik Rafidah; Sujud, Arba'ie; Dani, Noor Aina; Gani Hamzah, Mohd Sahandri (CG Publisher, 2009)
This research is carried out for the purpose of developing intercultural awareness, which should be one of the major aims of teaching English to young learners, along with learning how to speak or listen. Our presentation will report that reading picture-books in a foreign language to young children (5-6 years old) is effective in developing their consciousness about different languages or cultures. We had kindergartners read English picture-books more than three times a week, both in their kindergartens and at home, with some adults around them, and have found that this method helped them to be aware that there are many different sounds, words, and rhythms. This awareness may lead them to further consciousness of the existence of different cultures, and of different people belonging to them. This kind of intercultural awareness is important particularly in a mono-lingual society like Malaysia, where children are normally not exposed to different languages other than their mother tongue. Analysis of our interviews and questionnaires indicates that children who read English picture-books with CDs both in kindergartens and at home more than three times a week could develop an interest in and positive attitudes towards different languages and the people speaking them, and also the deeper culture on which they are based.